2010
DOI: 10.1089/end.2009.0367
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Partial Cystectomy for Bladder Cancer: A Single-Institutional Pilot Study

Abstract: RPC is technically feasible using the da Vinci Surgical Robotic System in select patients with bladder cancer without disease recurrence in the short term. A larger cohort with long-term follow-up is necessary to validate our results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 25 publications
1
27
0
Order By: Relevance
“…Therefore, Allaparthi and his team concluded that their early study showed promise that SCRPC is technically feasible for select patients with bladder cancer and the procedure shows adequate short-term oncological results [22]. We had comparable results at our institution with SCRPC in three patients as well, with mean EBL, hospital stay and mean operative time all within satisfactory limits [32].…”
Section: Oncological Outcomesmentioning
confidence: 83%
See 2 more Smart Citations
“…Therefore, Allaparthi and his team concluded that their early study showed promise that SCRPC is technically feasible for select patients with bladder cancer and the procedure shows adequate short-term oncological results [22]. We had comparable results at our institution with SCRPC in three patients as well, with mean EBL, hospital stay and mean operative time all within satisfactory limits [32].…”
Section: Oncological Outcomesmentioning
confidence: 83%
“…Guru et al also performed SCRRC on twenty consecutive patients between 2005 and 2006 and concluded that the procedure can be performed safely for candidates for open cystectomy [21]. In 2010, Allaparthi et al reported on a consecutive cohort of three patients undergoing surgeon-controlled robotic partial cystectomy (SCRPC) for bladder cancer which expanded the scope of this exciting new treatment modaility [22].…”
Section: Bladder Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…6 However, the largest, and more recent, study of UA to date reported more modest recurrence rates; 15% of patients with non-metastatic UA developed local recurrence, and this was usually after partial cystectomy. 1 However, there was no difference in survival rates between patients who underwent partial cystectomy versus radical cystectomy.…”
Section: Discussionmentioning
confidence: 99%
“…5 In 2010 Allaparthi's team published the successful short-term outcome of a patient with UA who underwent robotic PC (RPC). 6 Here we present the case of a patient with metastatic UA who underwent robotic PC who is alive with no evidence of disease recurrence or metastatic disease at 5 years.…”
Section: Introductionmentioning
confidence: 99%